Critical theory and legal autopoiesis the case for societal constitutionalism - Teubner, Gunther (Critical theory and contemporary society., 2019)
This volume collects and revises the key essays of Gunther Teubner, one of the world's leading sociologists of law. Written over the past twenty years, these essays examine the 'dark side' of functional differentiation and the prospects of societal constitutionalism as a possible remedy. Teubner's claim is that critical accounts of law and society require reformulation in the light of the sophisticated diagnoses of late modernity in the writings of Niklas Luhmann, Jacques Derrida and select examples of modernist literature. Autopoiesis, deconstruction and other post-foundational epistemological and political realities compel us to confront the fact that fundamental democratic concepts such as law and justice can no longer be based on theories of stringent argumentation or analytical philosophy. We must now approach law in terms of contingency and self-subversion rather than in terms of logical consistency and rational coherence.